Relationship between Socio-economic Factors and Electrical Energy Consumption of Customer Groups in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2024)
The research aim was to study Socio-Economic Analysis and its Relationship with Electrical Energy Consumption of Customer Groups in Indonesia using secondary data from 2018-2022 covering 34 provinces in Indonesia. Data sources generally come from Central Bureau of Statistics (BPS) and State Electricity Company (PLN) Indonesia. The results of the analysis show that GDP per capita, education and MSMEs have a significant negative influence on poverty in Indonesia. Furthermore, GDP per capita is the only variable that has a significant positive effect on electricity consumption, while education, MSMEs and poverty have no effect on residential electricity consumption. In the industry group, all variables have a significant effect on household consumption, except for education which has an insignificant effect, GDP per capita and MSMEs have a significant positive effect on electricity consumption, apart from that, education and poverty also have an effect but are not significant in the Business group. The research results also show that poverty does not have a significant impact, but GDP per capita, education and MSMEs have a significant positive influence on social electricity consumption. Furthermore, in the Government Office Buildings (GOB) group, GDP per capita and MSMEs have a significant positive effect, however, education and poverty do not have an influence on electricity consumption in this group. Finally, in the Public Street Lighting (PSL) group, GDP per capita, MSMEs and poverty have no effect, but MSMEs have an influence on electricity consumption.